PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI BAGIAN SUMBER DAYA MANUSIA PADA KANTOR PTPN VI KAYU ARO KABUPATEN KERINCI PROVINSI JAMBI - Sari, Desi Purnama (RC-INSTITUT, 2018)
The title of this research is the Effect of Motivation and Work Environment on Employee Performance At Office PTPN Vi KayuAroKerinci In the Human Resources (HR), this research aims to see Influence Motivation and Work Environment on Employee Performance At Office PTPN VI KayuAro District Kerinci In the Human Resources (HR). This study uses a quantitative method, because researchers want to measure between variables X1, X2 and Y. The sample in this research 33 people.The sampling technique saturation sampling research instrument in the form of questionnaires. Engineering analysis of the use of hypothesis testing Correlation Simple Linear and multiple linear regression, so that in can t 8.322> t table 2.040 (motivation) and the influence between Motivation on Employee Performance At Office PTPN VI KayuAroKerinci In the Human Resources (HR) amounted to 84.2% while the remaining 15.8% can be explained by other causes. Conclusion Ha Ho accepted and rejected, in other words there Effect of Employee Performance at the Office PTPN Vi KayuAroKerinci In the Human Resources (HR), and also can t 23.274> t table 2.040 (Working Environment) and the great influence of the Environment Work on Employee Performance at PTPN VI Office Kayu Aro Kerinci In the Human Resources (HR) of 97.7% while the remaining 2.3% can be explained by other causes. Conclusion Ha Ho accepted and rejected, in other words there is a working environment Effect on Employee Performance at PTPN VI Office KayuAroKerinci In the Human Resources (HR) and can also count 457.621 t> t table 3.32 (Motivation and Work Environment ) and the influence between Motivation and Work Environment on Employee Performance at PTPN VI Office KayuAroKerinci In the Human Resources (HR) of 98.7% while the remaining 1.3% can be explained by other causes. Conclusion Ha Ho accepted and rejected, in other words there between Motivation And Environmental Effects of Employee Performance at PTPN VI Office Kayu Aro Kerinci In the Human Resources (HR).